(untitled) (Innovative professional education, 2023)
The question of creating a modern scientific and methodological system of the lyceum, which ensures the continuity of the development of the research competence of the philologist teacher, is revealed and described. An analysis of the forms of pedagogical interaction for the professional development of the teacher of Ukrainian language and literature was carried out. The peculiarities of research activity are highlighted. The own vision of the prospects of the teacher’s professional development in the modern system of scientific and methodical work is formulated.